Serum and synovial fluid levels of angiotensin converting enzyme in polyarthritis. - Lowe, J R (1986)
Serum levels of angiotensin converting enzyme (ACE) activity in patients with rheumatoid arthritis (RA) (n = 48), osteoarthritis (OA) (n = 11), ankylosing spondylitis (n = 24), psoriatic arthritis (n = 12), and Behçet's syndrome (n = 20) were not significantly different from those of normal controls (n = 26). Synovial fluid ACE activity was lower in OA than in RA but was similar when corrected for protein levels. An increase in serum ACE concentration in patients with RA receiving captopril therapy is in agreement with previous results. There was some correlation of ACE with erythrocyte sedimentation rate (ESR) and C reactive protein (CRP) but not with clinical indices in captopril treated patients. It is suggested that the beneficial actions of captopril in the treatment of RA are not due to its activity as an ACE inhibitor, but more probably a result of captopril being an aliphatic thiol.